Ocular complications of the diabetes – diagnostic and therapeutic implications - Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Autor describe actual knowledge about diabetes epidemiology and ocular complications in course of diabetes. More information about innovation diabetic macular edema treatment is done.